1999
DOI: 10.1007/s11627-999-0023-z
|View full text |Cite
|
Sign up to set email alerts
|

The use of histology in the study of plant tissue culture systems—Some practical comments

Abstract: Histological methods have contributed significantly to our understanding of in vitro culture systems. A good histological study based on anatomical and histochemicai changes provides insight into cellular processes and provides clues that allow for the proposal of hypotheses for further experimentation. This article serves to draw attention to the use of a histological approach to one's experimental system. Some of the common mistakes in the handling and processing of explants are discussed. A protocol for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
12

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(72 citation statements)
references
References 19 publications
(20 reference statements)
0
60
0
12
Order By: Relevance
“…Structural studies during embryo development were conducted exactly as reported by Yeung (1999). Measurements of endogenous ascorbate and the enzymatic reactions of ascorbate peroxidase (APX), dehydroascorbate reductase (DHAR), glutathione reductase (GR), and monodehydroascorbate reductase (MDHAR) were carried out according to Stasolla and Yeung (2001) and Belmonte et al (2006).…”
Section: Histological Analyses and Ascorbate Metabolismmentioning
confidence: 99%
“…Structural studies during embryo development were conducted exactly as reported by Yeung (1999). Measurements of endogenous ascorbate and the enzymatic reactions of ascorbate peroxidase (APX), dehydroascorbate reductase (DHAR), glutathione reductase (GR), and monodehydroascorbate reductase (MDHAR) were carried out according to Stasolla and Yeung (2001) and Belmonte et al (2006).…”
Section: Histological Analyses and Ascorbate Metabolismmentioning
confidence: 99%
“…Proper classification of regenerating structures is essential for optimization of propagation procedures, and this requires histological analysis of serial sections (Yeung 1999;Haensch 2004). However, the majority of studies mainly describe protocols for plant regeneration but do not concern the histological characteristics of the process.…”
Section: Histology Of Regenerating Structuresmentioning
confidence: 99%
“…Pinto et al (2002) for the first time described a reproducible protocol for SE in E. globulus from mature embryos. Histological analysis is a powerful tool when developing new methods for organogenesis or SE procedures (Yeung 1999). Since the biological specimens are three-dimensional objects, conclusions based on two-dimensional sections, without taking into consideration the third dimension, can easily lead to mistaken conclusions (Yeung 1999).…”
Section: Two-leaf-stage Shootmentioning
confidence: 99%
See 1 more Smart Citation
“…For the histological examination of tissues and the histochemical localization of GUS staining in seedlings and anthers, fixed plant samples of different developmental stages of pBa002a-AtPAP15 F2-GUS lines were dehydrated through a graded ethanol series and embedded in Historesin (Yeung, 1999). Serial sections, 3 mm thick, were cut using a Ralph knife on a Reichert-Jung 2040 Autocut rotary microtome.…”
Section: Histochemical Analysis Of Gus Expressionmentioning
confidence: 99%